EFFECT OF COATING ON THE SPECIFIC PROPERTIES AND DAMPING LOSS FACTOR OF ULTEM 1010 - sara mohamad ahmad; Safeen Yaseen Ezdeen (Zanco Journal of Pure and Applied Sciences, 2021)
The dynamic analysis of the fused deposition modeling (FDM) products is one of the most important topics in investigation of 3D manufacturing nowadays. The purpose of this paper to present the dynamic properties of FDM parts made from ULTEM 1010 with different coating layer thicknesses. The coating process consists of two stages: physical vapor deposition (PVD) to pre-coat the samples with a thin layer of Cu and Cr to prepare samples for the next step, electroplating different layer thickness Cu an outer layer of Ni. COMSOL Multiphysics software is used for finite element analysis of the models for free and forced vibration. The results showed an increase in ultimate tensile strength and Young's modulus with increasing coating thickness. The effect of different coating layer thickness on the natural frequency and damping loss factor was studied. The scanning electron microscope was used to investigate the coating layers in tensile specimens after failure.